Recent advances in prebiotics: Classification, mechanisms, and health applications - Sajid Ali; Muhammad Hamayun; Muhammad Siraj; Sumera Afzal Khan; Ho-Youn Kim; Bokyung Lee (Future Foods)
Background: Prebiotics are non-digestible food components that selectively stimulate the growth and activity of beneficial gut microbes, offering a range of health benefits. Findings: This review highlights recent advancements in prebiotic research, focusing on their classification, mechanisms of action, and health applications. It covers traditional prebiotics, such as inulin and oligosaccharides, as well as emerging prebiotics like polyphenols. The review also explores innovations in formulation technologies, including microencapsulation and synbiotics. Clinical evidence supporting the roles of prebiotics in digestive, metabolic, immune, and mental health is presented. Additionally, regulatory considerations and safety profiles are examined, emphasizing the current regulatory frameworks and the need for standardized guidelines. Conclusion: Future research should prioritize personalized nutrition and precision medicine to fully harness the potential of prebiotics. This review lays the groundwork for continued innovation in prebiotic research and application, advancing our understanding of their evolving role and their impact on health.